PERANCANGAN KONTROLER PID PREDIKTIF ROBOT MODEL SEGWAY - Tri Hendrawan Budianto (Jurnal Ecotipe (Electronic, Control, Telecommunication, Information, and Power Engineering), 2014)
The segway plant has a certain load change and noise thus requare a controller that can handle both these problems. PID controller is able to control the plant when angle inclination changes that occurred not too large. For the PID, the value of sensor variables are angle elevation, then its parameters estimation problem is also different from the estimation of the parameters that are not angle valued, the reason is the nonexistence of linearity from data accelerometer sensor. This robot has ability to maintain balance with two wheels and work at an angle of -8 degrees to +8 degrees to obtain a balance.